Analysis of Top-K Query for Data Stream Using Classification Adaptive Model - Nalini, M; kuruvilla, Anjali (International Journal of Computer Sciences and Engineering, 2025)
Data stream classification has been a wide studied detailed examination downside in recent years. The vigorous and evolving nature of knowledge streams needs economical and effective techniques that square measure considerably completely different from static data classification techniques. The foremost strenuous and well studied characteristics of information streams square measure its infinite length and concept-drift. Information stream classification poses several challenges to the info mining community. All through this paper, we enclose a affinity to talk four such major dispute namely, IL, CDI, CE, and FE. Since an information stream is in theory IL Model (Infinite long), it's impractical to store and use all the historical information for coaching. CD Model (Concept-Drift) could be a common development in information streams that happens as a result of changes within the underlying ideas. CE (Concept-Evolution) happens as a results of new categories evolving within the stream. Feature-evolution (FE) Model could be a oft occurring method in several streams, reminiscent of text streams, within which new options seem because the stream progresses. Most existing information stream classification techniques address solely the primary challenges, and ignore the latter two. The paper proposes associate degree ensemble classification framework, wherever every classifier is provided with a unique class detector, to handle CE